Implementasi Kebijakan Pengembangan Potensi Wisata Sungai Bukit Lawang Pada Dinas Pariwisata Kabupaten Langkat - Nadya Sri Astuti; Novita Wulandari; Khairunnisa Lubis (Universitas Medan Area, 2023)
This research is motivated by the not yet optimal implementation of policies regarding development of the Sungai Bukit Lawang Tourism Destination by the Langkat Regency Tourism Office. This is due to the lack of facilities and infrastructure to support tourism development. This study aims to describe and determine the implementation of policies at the Langkat Regency Tourism Office. As well as to find out the supporting and inhibiting factors of policy implementation at the Langkat Regency Tourism Office. This study analyzes first by analysis (Edwards III, 1980: 1). The research method used is descriptive qualitative method. The informants of this study were 7 informants. Data collection techniques using field studies (observations, interviews, and documentation).This can be seen based on the opinion of the informant who stated that there is still a lack of facilities and infrastructure provided directly by the agency. There are perceived obstacles such as budget constraints, difficulty applying tasks according to SOP to the community.Â